Assessment of Patch Test in Predicting Ossicular Status in Chronic Otitis Media - Bhandari, Shama; Parajuli, S.; Saxena, R. K. (Journal of Nepalgunj Medical College, 2017)
Objectives: To assess the reliability of paper-patch test in predicting the intra-operative ossicular status of patients with tympanic th membrane perforation from small to medium size. Methods: This is a hospital based prospective study conducted from 30 April, st 2016 to 1 May, 2017 in the Department of Otorhinolaryngology of Nepalgunj Medical College Teaching Hospital. The patients of chronic otitis media with small to medium sized central perforation were subjected to complete history taking and thorough examination. Audiological evaluation was done before patching, then after patching the perforation with cigarette paper. The result was recorded to predict the ossicular status. Result: The most common age group affected by the disease was 20-30 years with 21(42%) patients. Most of them were females 28(56%). Left ear was affected more 19(38%) than right ear 16(32%) and bilateral 15(30%). All the patients had conductive type of hearing loss out of which moderate degree of hearing loss was present in 36(72%) and mild degree of hearing was present in 14(28%). Following patch test, the hearing improved and in 7(14%) of patients the hearing came to normalcy. Majority of patients had mild degree of hearing loss, i.e., 36(72%) and moderate degree of hearing loss was seen in 7(14%). It was found that in those patients in whom there was less improvement in hearing that i.e. less than 10 dB, the mobility of the ossicles was restricted intra-operatively. Conclusion: The type of hearing loss was conductive hearing loss out of which most common was moderate degree of hearing loss in 36(72%) followed by mild degree of hearing present in 14(28%). Following patch test, it was found that in those patients in whom there was less improvement in hearing i.e., less than 10 dB,ossicular discontinuity was noted intra-operatively and thus ossicular reconstruction by tympanoplasty procedures had to be undertaken.